Peningkatan Motivasi Belajar Siswa dengan Menggunakan Media Buku Cerita Bergambar Edukatif di Sekolah Dasar - Arisma Salwa Hilmana; Muhaiminah Jalal (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is Class Action Research (PTK), set at State Elementary School 125/IX Simpang Selat. The objects of this research were class III students at State Elementary School 125/IX Simpang Selat, and the aim of this research was to apply educational picture story book media to the learning of Natural and Social Sciences (IPAS), animal life cycle material. This research was carried out in two cycles and four stages, including: (1) planning, (2) implementation, (3) observation, (4) reflection. Data was obtained through observation, interviews and documentation. Using qualitative and quantitative data analysis. The results of the research show that the application of educational picture storybook media can increase students' learning motivation in the learning process. Increased learning motivation can be measured from assessments in Cycle I and Cycle II. The student learning motivation score in cycle I was 52% in the high category, and the student learning motivation score in cycle II was 82% in the very high category. Therefore, the research results at State Elementary School 125/IX Simpang Selat have been well realized.